On-Site Dual Detection of Airborne Acinetobacter baumannii and Its Carbapenem-Resistant Gene blaOXA-23 Using a One-Pot Visual LAMP-CRISPR/Cas12a-Based Platform - Huijun Lu; Tong Zhang; Wei Huang; Jinhui Zhu; Haoran Qin; Xi Chen; Wang Zhao; Guodong Sui (Microorganisms)
Acinetobacter baumannii (A. baumannii), a very common pathogen, poses a significant public health threat due to its antibiotic resistance and long survival in healthcare environments. Both A. baumannii and carbapenem-resistant A. baumannii (CRAB) can spread through the air, increasing infection risks. Therefore, monitoring their presence in the air is of great significance, especially in hospitals. Herein, we developed a Chelex-100-LAMP-CRISPR/Cas12a (CLC) platform including DNA release and nucleic acid test. Combined with a wet cyclone sampler, the platform can detect airborne A. baumannii and its most common carbapenem-resistant gene, blaOXA-23, within 70 min. This CLC platform has also been proven to have a detection limit of 6 × 102 CFU of CRAB per test through simulated air samples. Moreover, this platform was also used to test five actual air samples from a tertiary hospital, and the results achieved perfect concordance with sequencing data, validating the platform’s accuracy and reliability. Therefore, the CLC platform showed great potential for the rapid, on-site detection of airborne A. baumannii and its carbapenem-resistant gene blaOXA-23, offering a valuable tool for infection control in healthcare environments.